Neurovirulent simian immunodeficiency virus infection induces neuronal, endothelial, and glial apoptosis. - Adamson, D. C. (The Feinstein Institute for Medical Research, 1996)
BACKGROUND: Studies of human immunodeficiency virus type 1 (HIV-1) associated dementia have shown neuronal loss in discrete areas. The presence and mechanism of neuronal death, however, has remained quite elusive. One mechanism of cell death, apoptosis, has been clearly demonstrated outside the central nervous system (CNS) in HIV-1 infection but has not been firmly established within the CNS. Therefore, we set out to ascertain whether neuronal cell loss in simian immunodeficiency virus (SIV) encephalitis, an animal model of HIV-1-associated dementia, is a result of apoptosis. MATERIALS AND METHODS: With the aid of an in situ technique for identifying the 3'-OH ends of newly fragmented DNA characteristic of apoptosis, in conjunction with specific detected morphological criteria via light microscopy, we have examined encephalitic and nonencephalitic brains of macaques infected with a neurovirulent, neuroendotheliotropic strain of SIV to see if virus is spatially associated with apoptosis of neurons and non-neuronal cell types. RESULTS: We demonstrate the presence of DNA damage, indicative of apoptosis, in neurons, endothelial cells, and glial cells of the CNS of SIV-infected macaques. Furthermore, we observe an association between the localization of cells with significant DNA fragmentation and perivascular inflammatory cell infiltrates containing SIV-infected macrophages and multinucleated giant cells. Quantitative analysis reveals significantly more cells with DNA fragmentation in the CNS of macaques infected with neurovirulent, neuroendotheliotropic SIV strains as compared with strictly lymphocyte-tropic SIV strains and SIV negative controls. CONCLUSIONS: Our findings of apoptosis in SIV-infected CNS may potentially lead to a better understanding of the AIDS dementia complex, ultimately providing a basis for better treatments.